Social Dimensions in Robert Galbraith's Novel "Troubled Blood" by J.K. Rowling and Their Relevance to Moral Messages - Rohman, Ahmad Sani Saefur; Wahyudi, Agus Budi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This article aims to explore the social dimensions embodied by Private Detective Cormoran Strike in Robert Galbraith's novel 'Troubled Blood,' examining their relevance to moral messages. Methodology: The research employs a qualitative descriptive method, utilizing literature review techniques for data collection. Data validation is achieved through source triangulation, and analysis adopts a semiotic reading approach. The process involves reading, analyzing, presenting, and drawing conclusions from the obtained data. Results: The article's findings include: (1) Various forms of physical violence such as stomping, shoving, torture, whipping, cutting, slashing, shackling, force-feeding, and dragging. (2) Psychological violence manifested through insults, shouting, and unpleasant statements. (3) Sexual violence, notably rape. (4) These research results are pertinent to the moral message category concerning human relationships within the social environment. Applications/Originality/Value: J.K. Rowling's novel "Troubled Blood," written under the pseudonym Robert Galbraith, is a literary work that depicts various social dimensions in London society. This article aims to analyze various aspects of social dimensions within the novel and explore their relevance to the moral messages conveyed by the author. Using a literary analysis approach, this article will discuss how the portrayal of social dimensions in "Troubled Blood" can provide a deeper understanding of the moral messages the author intends to convey. "Troubled Blood" is part of the Cormoran Strike series written by J.K. Rowling under the pseudonym Robert Galbraith. The novel follows the adventures of detective Cormoran Strike and his assistant, Robin Ellacott, in solving mysterious murder cases. In addition to focusing on the criminal plot, the novel also depicts various aspects of social life in London.